2010
DOI: 10.1017/s0033291710002412
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in connectivity of white-matter tracts in patients with familial and non-familial schizophrenia

Abstract: Overall, these findings support the hypothesis that loss of WM integrity may be an important pathophysiological feature of schizophrenia, with particular implications for brain dysmaturation in non-familial and familial schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 73 publications
5
30
0
Order By: Relevance
“…Thirty of the 68 patients in this study were neuroleptic-naïve at the time of DTI, and the remaining 38 patients were on low dose antipsychotics at least 3 days prior to MRI scanning. There are no significant differences in FA values between the neuroleptic-naïve patients and patients on medication (Wang et al, 2011). DTI reports offer additional support to neuropsychology, and volumetric and functional neuroimaging studies that have implicated frontal and temporal lobe abnormalities in schizophrenia.…”
Section: Pathological Changes Of White Matter In Schizophreniamentioning
confidence: 73%
See 1 more Smart Citation
“…Thirty of the 68 patients in this study were neuroleptic-naïve at the time of DTI, and the remaining 38 patients were on low dose antipsychotics at least 3 days prior to MRI scanning. There are no significant differences in FA values between the neuroleptic-naïve patients and patients on medication (Wang et al, 2011). DTI reports offer additional support to neuropsychology, and volumetric and functional neuroimaging studies that have implicated frontal and temporal lobe abnormalities in schizophrenia.…”
Section: Pathological Changes Of White Matter In Schizophreniamentioning
confidence: 73%
“…The authors concluded that there were abnormalities in the fronto-limbic circuitry at the earliest clinical stages of schizophrenia (Yao et al, 2013). Wang et al (2011) also reported FA deficits in the right corpus callosum as well as the left temporal lobe of schizophrenia patients. Thirty of the 68 patients in this study were neuroleptic-naïve at the time of DTI, and the remaining 38 patients were on low dose antipsychotics at least 3 days prior to MRI scanning.…”
Section: Pathological Changes Of White Matter In Schizophreniamentioning
confidence: 99%
“…It has been suggested that the pathophysiology of schizophrenia may lie in abnormal interactions or dysconnectivity across a distributed network of brain regions (Stephan et al 2006;Segal et al 2007). Consistent with this, cross-sectional studies have shown the presence of structural brain abnormalities in the early phase of schizophrenic illness (Federspiel et al 2006;Kanaan et al 2006;Peters et al 2010;Wang et al 2011), although several studies failed to detect structural brain anomalies in early-episode patients (Moncrieff & Leo, 2010). More extensive structural brain abnormalities were found in chronic patients with schizophrenia, which may reflect the progressive nature of this condition .…”
Section: Introductionmentioning
confidence: 87%
“…As an essential component of the plasticity of neuronal circuits, myelin sheaths insulate and propagate electrical signals rapidly along axons [7] . More importantly, properly myelinated nerve fibers allow precise and accurate information to fl ow within and between neuronal circuits [3,8,9] . A number of imaging studies have shown that the white matter volume of schizophrenic brains is lower than in healthy controls, suggesting that myelin sheath damage or demyelination is involved in the schizophrenic brain [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%